Nothing but trouble - Davies, Jacqueline, 1962- (New York : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2016)
"Two smart girls in one small town use their combined genius to liven up their world--one prank at a time"--
Ages 8-12.
Keywords: Friendship -- Juvenile fiction; Practical jokes -- Juvenile fiction; Middle schools -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Fiction; Practical jokes -- Fiction; Middle schools -- Fiction; Schools -- Fiction; Humorous stories; Humorous stories; Friendship -- Juvenile fiction; Friendship -- Fiction; Middle schools -- Juvenile fiction; Middle schools -- Fiction; Schools -- Juvenile fiction; Schools -- Fiction; Humorous fiction